Eksplorasi dan Karakteristik Bakteri Endofit Asal Tanaman Handeuleum (Graptophyllum pictum (L) Griff) - Manalu, Jean Nihana; Mariana, Maya (UNIVERSITAS LABUHANBATU, 2023)
Handeuleum (Graptophyllum pictum L. Griff) is a plant that is used as a medicinal plant with secondary metabolite compounds so that it can overcome several diseases. Exploration of endophytic bacteria in handeuleum plants needs to be done, because the content of secondary metabolites can be used to suppress the growth of plant pathogens.The purpose of this study was to obtain isolates of endophytic bacteria and find out their characteristics. This research was conducted with an exploratory method that began with the isolation of endophytic bacteria and several tests were carried out such as hemolysis activity, hypersensitivity, gram test, chitinolytic test, phosphate solvent activity, and antagonist test.The isolation results obtained a high population of endophytic bacterial isolates, namely in the roots, as many as 8 isolates that are pathogenic in mammals, hypersensitivity tests showed no isolates that were pathogenic in plants, gram tests obtained as many as 24 isolates that were gram-positive, as many as 5 isolates were able to lyse phosphate, no isolates could degrade chitin, as many as 2 isolates were antimicrobial against Rastolnia solanacearum indicated by the presence of clear zones and 26 isolates were able to suppress the growth of Fusarium oxysporum.Â Keywords: Antimicrobial, pathogenic, hemolysis, hypersensitive, chitinolytic